The influence of disability-friendly corporate branding on company brand equity in East Java - Junianta Reynaldi Dwi; Iriani Sri Setyo; Nugrohoseno Dwiarko; Nuswantara Dian Anita (E3S Web of Conferences, 2023)
This research analyzed the influence of disability-friendly corporate branding on corporate brand equity. Corporate branding is built through corporate values, corporate image, and corporate culture. This research uses a quantitative approach, with a population of corporate employees and customers in East Java. A purposive sampling technique was used to take samples from the population with the following criteria: (1) located in the East Java region; (2) an area with Special Needs High School with more than 50 students; (3) data recorded in the industrial directory in East Java Province region. A total of 180 respondents were obtained through distributing questionnaires online. The research data was then processed using SEM-AMOS to carry out analysis. The research results show that there is a significant influence of disability-friendly corporate branding on corporate brand equity. This research conducted research on company efforts to create disability-friendly branding for their companies using a corporate branding approach. Companies need to carry out corporate branding by through implementing the values of inclusivity, a corporate image that cares for people with disabilities, and a culture of equality. This will help companies to increase corporate brand equity which can provide company benefits that contribute to the implementation of SDGs 4, 8, and 10.